Healthcare without borders : understanding Cuban medical internationalism - Kirk, John M., 1951- (Contemporary Cuba., 2015)
Over the course of the last five decades, Cuba has been a leading force in the developing world via medical internationalism, providing humanitarian aid and initiating programs for preventative care and medical training. In this book, John Kirk argues that Cuba's medical internationalism is one of its best-kept secrets, and he explores the philosophical underpinning about access to medical care at the core of Cuba's medical internationalism programs.